Rattus norvegiens - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus norvégiens (Berkenhout, 1769). Outlines Nat. Hist. Great Britain and Ireland, 1:5 (N.V.). REVIEWED BY: M. Andera (MA); O. L. Rossolimo (OLR)(U.S. S.R.); G. Urbano-V. (GUV). TYPE LOCALITY: Great Britain. DISTRIBUTION: Original distribution assumed to be S.E. Siberia and N. China; introduced worldwide. COMMENT: Includes magnirostris; see Musser, 1977, Am. Mus. Novit., 2624:12. Includes insolatus; see Jones and Johnson, 1965, Univ. Kans. Publ. Mus. Nat. Hist., 16:389. ISIS NUMBER: 5301410011058082001 as R. norvegicus. 5301410011058066001 as R. magnirostris. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on pages 551-552, DOI: 10.5281/zenodo.7353037